Oil revenues and economic growth in Ecuador (2000-2015) - Cepeda Chacaguasay, Pedro (2016)
This research attempts to explain economic growth in Ecuador from oil revenues, since in the last ten years the oil sector and economic growth have attracted attention in the literature; its importance refers to the theory of Solow growth. The main variables analyzed were oil revenues, as a key variable in the production function, it was estimated per capita terms per worker; for this, statistical series Central Bank of Ecuador and ordinary least squares were used; Also, the gross ﬁxed capital formation, economically active population and oil revenues, the latter as a foreign additional variable production function to explain economic growth. As a main result a positive relationship GDP per worker (y) with the gross ﬁxed capital formation per worker (k) and oil income per worker (yp) is obtained, when the variables investment and income increase, GDP per worker also increases.